Experimental study on the efficiency improvement of flat plate solar collectors using hybrid nanofluids graphene/waste cotton - Mahamude, Abu Shadate Faisal; Wan Sharuzi, Wan Harun; Kadirgama, Kumaran; Ramasamy, Devarajan; Farhana, Kaniz; Khalid, Saleh; Yusaf, Talal (MDPI AG, 2022)
Flat plate solar collectors can easily be termed as the most vastly studied alternative energy transforming and generating technology of the twenty-first century. As the world is racing towards the fourth industrial revolution (Industry 4.0), more and more energy is being consumed for mega projects to be materialized. Electronic devices are not only confined to conventional intermittent and costlier electric energy, but also fuel. Solar energy is now being shared to work smart devices, transform electric energy, and operate automobiles, aeronautics, water heating, and space heating. Traditional flat plate solar collectors can only occupy 50–60% of their thermal efficiency, resulting in less heat generation and a low thermal performance because of using a common absorber made of copper tubing compared to a high conductive metal sheet (copper or aluminum). To ameliorate the thermal efficiency of the solar collector, it is imperative to find a superior alternative heat exchanger that will result in improved thermal performance of the solar collector. In this study, light has been shed in terms of substituting conventional heat absorbers with crystal nano-cellulose (CNC) and a graphene hybrid. An empirical comparison has been drawn by comparing the familiar 0.3% base fluid, 0.5% graphene, and CNC separately, as well as 0.3%, 0.5% CNC, and graphene hybrids at different temperatures. Remarkably, this work has proven that a CNC and graphene hybrid fluid with a volumetric fraction of 0.5% concentration and at a high temperature of 80 °C, gave astounding results for improved thermal conductivity, viscosity, and other parameters. CNC and graphene hybrid nanofluid can be a superior substitute for a conventional base fluid, resulting in prolific thermal performance.